Reflections on a nursing education institution transitioning to online education during the Covid-19 pandemic - M.A. Jarvis; O.B. Baloyi (Elsevier, 2023)
In 2022, nursing faculty reflect on the transition without global or national benchmarks or blueprints of a South African Nursing Education Institution to online education during the Covid-19 pandemic. Objective: To provide policy makers a resource in preparation for future crises in education. A theoretical-reflective study supported by a SWOT analysis aimed to understand the transition to online teaching and learning and assessments for the Nursing Discipline (nursing faculty n = 22; undergraduate students n = 291) of a select South African university. It revealed four key lessons learned. Firstly, whether change is planned or unplanned, policy frameworks should guide it. Secondly, resources exist within faculty, and at times, change agents might not be necessary as strengths can be drawn from within. Thirdly, through managing a crisis, faculty-service partnership can be strengthened. Lastly, a need exists for continual surveillance as the inequality gap in Higher Education students has become increasingly visible and amplified further marginalisation. Our reflections have highlighted that opportunities and strengths abound as the pandemic has fast-tracked nursing education institutions to embrace technology for teaching and learning and assessments. Three of the key lessons learned emphasise what is known about the successful outcome of working together.